Lexical Interference: Mandailing and English Language Speech of Gunung Tua Padang Bolak Native Speakers - Aditia, Dedek; Zulkarnain, Iskandar; Harahap, Yunita Mutiara (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
This study investigates lexical interference among Mandailing speakers when using English, focusing on the causes and strategies to reduce this interference. The research targets native Mandailing speakers in Gunung Tua Padang Bolak who actively use English. The study aims to identify the factors that lead to lexical interference between Mandailing and English and to explore strategies for reducing it. A qualitative descriptive approach was employed, with data collected through observations and interviews with five students, recommended by local authorities for their active use of English. The study reveals that the dominance of the Mandailing language in daily communication is a significant factor causing lexical interference. Students often blend Mandailing terms into their English speech, which leads to errors in pronunciation, structure, and grammar The findings highlight that this interference is exacerbated by limited exposure to English and the strong cultural ties to the Mandailing language. However, strategies such as language immersion, targeted vocabulary expansion, and increased awareness of language use have been effective in reducing this interference. The research emphasizes the importance of understanding the linguistic and cultural dynamics in bilingual settings to improve English language proficiency among Mandailing speakers.